Design and Implementation of Cardiopulmonary Resuscitation Simulation Model - Mkiramweni, Mbazingwa; Rugumira, Georgia; Msangi, Napendael (Tanzania Journal of Engineering and Technology, 2022)
Cardiopulmonary resuscitation (CPR) is a life-saving procedure that can multiply a person's chances of survival after a cardiac arrest. The effectiveness of CPR procedures is heavily influenced by the individual skills of the rescuer providing assistance. Chest compressions delivered at an appropriate depth and rate, allowing full chest recoil and with minimal interruptions, are critical for improving cardiac arrest survival. The lack of quality CPR training models in developing countries has a significant impact on the quality of CPR training and skills acquired. Therefore, in this paper, we aim at improving CPR training by designing a high-fidelity CPR training manikin. The model includes a feedback mechanism for monitoring CPR performance status to allow for effective practice and rehearsal until required CPR skills are acquired. An in-depth study of existing training systems was conducted to ensure the proper design of the proposed system. The test results show that the designed manikin prototype analyses the quality of CPR performance and provides appropriate feedback to the trainee. The model can be used for training medical students and other practitioners to correctly perform CPR.